2000
DOI: 10.1034/j.1600-0463.2000.d01-64.x
|View full text |Cite
|
Sign up to set email alerts
|

The immune response to chronic Pseudomonas aeruginosa lung infection in cystic fibrosis patients is predominantly of the Th2 type

Abstract: Most cystic fibrosis (CF) patients with chronic Pseudomonas aeruginosa lung infection have a persistent acute type lung inflammation dominated by polymorphonuclear neutrophils (PMN) and a pronounced antibody response against P. aeruginosa. We speculated whether this immune response in CF is of the Th2 type and whether a change to a Th1 type immune response could improve the prognosis. Therefore, we studied 14 CF patients with (CF +P) and 14 CF patients without (CF -P) chronic P. aeruginosa lung infection. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
148
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(157 citation statements)
references
References 23 publications
7
148
1
1
Order By: Relevance
“…For example, Moser et al (43) have shown that the PBMCs of Pseudomonas-infected patients to have lower IFN-g and higher IL-4 production compared with cells from noninfected patients; they also showed that IFN-g production positively correlated with lung function. In addition, Hartl et al (7) reported that the bronchoalveolar lavage from chronically Pseudomonas-infected CF patients had significantly higher levels of Th2 lymphocytes, IL-4, and IL-13, while having lower levels of IFN-g compared with noninfected patients, and the levels of IL-4 and IL-13 correlated inversely with lung function (7).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Moser et al (43) have shown that the PBMCs of Pseudomonas-infected patients to have lower IFN-g and higher IL-4 production compared with cells from noninfected patients; they also showed that IFN-g production positively correlated with lung function. In addition, Hartl et al (7) reported that the bronchoalveolar lavage from chronically Pseudomonas-infected CF patients had significantly higher levels of Th2 lymphocytes, IL-4, and IL-13, while having lower levels of IFN-g compared with noninfected patients, and the levels of IL-4 and IL-13 correlated inversely with lung function (7).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous report on Staphylococcus aureus demonstrated that secretion of this cytokine by human leukocytes was induced within 2 h of exposure to S. aureus biofilms (7). Interestingly, Moser et al (48,49) have demonstrated that P. aeruginosa induces a Th2 type response in mouse models of CF yet to clear the infections, a Th1 response is required. IFN-␥, a Th1-type cytokine, was vital to P. aeruginosa algD Ϫ biofilm bacterial killing in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The significant increase in these ratios between the 24 and 48 h time-points is indicative of a Th1-based immune response (Table 3). The immune response in CF patients with chronic P. aeruginosa infections is predominantly a Th2 response and is correlated with a poor prognosis (Moser et al, 2000). It has been proposed that shifting the immune response to Th1 may help to combat P. aeruginosa infection (Høiby et al, 2001).…”
Section: Th1 Cytokines Are Up-regulated At 48 H Postinfectionmentioning
confidence: 99%